R. Dickenson journal - Dickenson, R.
Unbound journal (1828 January 19-1829 June 14) kept by Dickenson aboard the H.M.S. Wasp.
Seaman.
Collection material in English.
Keywords: Ship's papers -- 19th century; Wasp (Ship); Sailors